2010
DOI: 10.1519/jsc.0b013e3181ddb308
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic Muscle Activity in Curl-Up Exercises With Different Positions of Upper and Lower Extremities

Abstract: The purpose of the study was to evaluate the electromyographic (EMG) activity of muscles in curl-up exercises depending on the position of the upper and lower extremities. From the perspective of biomechanics, different positions of the extremities result in shifting the center of gravity and changing muscular loads in abdominal strength exercises. The subjects of the research were 3 healthy students (body mass 53-56 kg and height 163-165 cm) with no history of low back pain or abdominal surgery. Subjects comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
1
13
0
1
Order By: Relevance
“…The idea adopted in the study consists of increasing the load to the muscles through changing the external torque. It was supported by previous results where contribution of body trunk flexors and hip extensors in abdominal exercises performed in different angular positions of the lower and upper limbs was examined [16,17]. These studies have found that the change in position of the upper and lower limbs (change in length of the lever arm) and the change in the muscle torque (through changing the angle of the joint) cause a change in abdominal muscle activity.…”
Section: Discussionsupporting
confidence: 67%
“…The idea adopted in the study consists of increasing the load to the muscles through changing the external torque. It was supported by previous results where contribution of body trunk flexors and hip extensors in abdominal exercises performed in different angular positions of the lower and upper limbs was examined [16,17]. These studies have found that the change in position of the upper and lower limbs (change in length of the lever arm) and the change in the muscle torque (through changing the angle of the joint) cause a change in abdominal muscle activity.…”
Section: Discussionsupporting
confidence: 67%
“…In early studies, Arokoski, Valta, Airaksinen, and Kankaanpää (2001) reported the effects on abdominal muscle activity during the performance of upper-limb exercises; the activation patterns of the abdominal muscles were affected by the direction of restricted upper-limb movements. Other researchers have also reported that changes in position of the upper extremities enriched curl-up exercises due to change in abdominal load (Rutkowska-Kucharska, & Szpala, 2010). However, these exercises are difficult to use to strengthen abdominal muscles in stroke patients because many stroke patients cannot readily use the paretic upper limb.…”
Section: Introductionmentioning
confidence: 99%
“…Em função disso, investigações têm sido conduzidas a fim de determinar a maneira mais eficiente e correta de se realizar exercícios abdominais, principalmente por meio da eletromiografia de superfície [6][7][8][9][10] . Esta, segundo Basmajian e De Luca 11 , é o estudo da função muscular a partir da averiguação do sinal elétrico que emana do músculo.…”
Section: Introductionunclassified